STUDY OF THE SAFETY OF ANTIANEMIC PREPARATIONS BY METHOD OF THE SYSTEM OF PROBLEMS RELATED TO MEDICINAL PREPARATIONS - A. V. Matveev; E. A. Egorova; E. I. Konyaeva; E. Yu. Bekirova; L. A. Adjimamutova (Фармация и фармакология (Пятигорск))
Iron deficiency is the most common micronutrient deficiency worldwide. Prevention and treatment of iron deficiency conditions are some of the most important health problems in many countries of the world. At the same time, the main problems for it remain the timely diagnosis, elimination of the cause, as well as the choice of replacement therapy with iron-containing drugs and correction of adverse reactions (ADR) that occur during their use.The aim. This research aims to study the peculiarities of the development of antianaemic drugs ADRs in patients living in the territory of the Republic of Crimea.Materials and methods. The objects of research were cases of ADR occurrence associated with the use of a group of antianaemic drugs and revealed during the 2009-2018 period in the territory of the Republic of Crimea. The main tasks in the analysis of notification forms were the study of the ADR severity, the causality assessment for suspected drugs and ADRs, as well as analysis of particular problems associated with the use of antianaemic drugs (Drug-related problems, DRP).Results. Iron supplements in combination with other drugs became the leaders in the incidence of ADR among antianaemic drugs (28 cases, 42.4% of all cases of ADR). The largest number of cases was registered in patients aged from 18 to 30 years, with female patients prevailing. Among the clinical manifestations of ADR, the most cases were drug hypersensitivity reactions of varying severity (40 cases) and disorders of the gastrointestinal tract (18 cases). The study of the problems associated with the use of antianaemic drugs made it possible to determine that the highest rates of DRP values were observed with the use of iron preparations for parenteral use and cyanocobalamine. The minimal DRP values were observed when prescribing iron protein succinylate preparations.Conclusion. The basis of pharmacotherapy for various types of anemias is the replenishment of iron and vitamin B12 (cyanocobalamin) depots. The effectiveness of the treatment in these cases largely depends on the patient's adherence to treatment, which is, in turn, depends on the frequency and severity of ADRs that occur during the use of antianaemic drugs.